Heavy metal(loid)s contamination and health risk assessment of soil-rice system in rural and peri-urban areas of lower brahmaputra valley, northeast India. (March 2021) - Baruah, Sunitee Gohain; Ahmed, Imdadul; Das, Banashree; Ingtipi, Bhomtalika; Boruah, Himangshu; Gupta, Sanjay Kumar; Nema, Arvind K.; Chabukdhara, Mayuri
Abstract: The soil-rice system in rural and peri-urban areas of the lower Brahmaputra valley, northeast India was investigated for heavy metal(loid)s using Nemerow's pollution index ( PI N ) and potential ecological risk index ( RI ). Potential health risk due to rice consumption grown in the region was assessed in terms of carcinogenic and non-carcinogenic risks. Around 95% of the soil showed acidic nature that ranged from weakly acidic to strongly acidic soil. In terms of PI N, 27.3% of the sampling sites were heavily polluted ( PI N ≥3 ), 34.8% moderately, and 37.9% were slightly polluted. The Pb concentration was comparably higher in 57.1% of the rice grain samples and the mean As level (0.17 mg kg −1 ) was close to the WHO limit. The non-carcinogenic risk in terms of hazard quotient (HQ) was high primarily due to As (HQ > 1), whereas other metals had limited contribution (HQ < 1). The carcinogenic risk based on total cancer risk (TCR) values for adults and children ranged between 0.0039 – 0.019 and 0.0043–0.0211, respectively, exceeding the maximum acceptable level of 1 × 10 −4 . Among the rice varieties, for non-carcinogenic risks, the maximum hazard index (HI) was noticed for Bahadur and the minimum for Ranjit. Whereas for carcinogenic risks, the maximum TCR was observed for Mahsuri and the minimum for Moynagiri. Highlights: A comprehensive heavy metal pollution and health risk assessment of soil-rice system was conducted. Paddy soil showed acidic nature that ranged from strongly acidic to weakly acidic soil. Nemerow's pollution index showed slight to heavy pollution. Concentration of Cd and Fe in rice grains were correlated with their concentrations in the corresponding soil. Heavy metal pollution in rice indicated potential health risks to the consumers.